أمان طرائق التواقيع الرقمية - جركس, تاج الدين; معترماوي, عدنان; ناصر, غسان (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر التواقيع الرقمية إحدى أهم التطبيقات الحديثة للتعمية ومن أهم تقنيات تحقيق الأمان في المعاملات الإلكترونية الرقمية التي تتزايد أهميتها باستمرار في عصر الحوسبة والمعلوماتية. يهدف هذا البحث إلى دراسة مقارنة لأمان طرائق التواقيع الرقمية وذلك بعد دراسة التواقيع الرقمية ومتطلباتها وأنواعها وطرائقها. يتضمن البحث دراسة أمان أهم طرائق التواقيع الرقمية التي تقوم على خوارزميات المفتاح العام المبنيّة على أسس رياضية مختلفة وسنختار من أجل ذلك طريقتين مستخدمتين لإنشاء تواقيع المرة الواحدة و طرائق أخرى تقوم على مسألة اللوغاريتم المقطَّع بالإضافة إلى طريقة تقوم على مسألة تحليل الأعداد الكبيرة جداً إلى عواملها الأولية. كما يتضمن البحث اقتراح توصيات مناسبة لتحسين الأمان. Digital signatures is one of the most important new applications for cryptography and the most important technique of achieving security in digital transactions. Its importance increases continuously in the age of computing and informatics. This paper studies the security of digital signature schemes after studying the digital signatures and its requirements, types and schemes. The paper includes studying the security of the most important digital signature schemes, which depend on the public-key algorithms that are based on several mathematical bases. We will select for that two schemes used to produce one-time signatures and other schemes that depend on discrete logarithm problem, in addition to one scheme that depends on factoring very great numbers. The paper also includes suggestions for suitable recommendations to improve the security of digital signature schemes.